273 INTERNAL CAPSULE ABNORMALITIES ON NEONATAL BRAIN MRI ARE ASSOCIATED WITH LATER GAIT DISORDERS IN VERY LOW BIRTH WEIGHT PRETERM CHILDREN AT 4 YEARS. (1st January 2005) - Rose, J.; Mirmiran, M.; Butler, E. E.; Lin, C.; Barnes, P. D.; Kermoian, R.; Stevenson, D. K.; Ariagno, R. L.
Abstract : Objective: Our previous work has shown a correlation between near term fiber tract integrity in the posterior limb of the internal capsule, using the new diffusion tensor imaging (MRI-DTI), and neurological outcome at 18-24 mo of age in VLBW preterm children. The present study investigates the relation between the decrease in fractional anisotropy (FA) in the posterior limbs of the internal capsule and the severity of gait abnormalities at 4 y of age in VLBW preterm children. Methods: Preliminary data were collected on 20 VLBW preterm children at 4 y of age: 12 with brain MRI that was normal for preterm children and 8 with abnormal MRI. Severity of abnormality in posterior limb of internal capsule was determined by reduced FA, a measure of neuronal fiber organization and myelination. The severity of gait abnormalities was determined using the primary outcome measure, the Normalcy Index (NI), a single score based on 16 kinematic parameters that quantifies the amount by which a subject's walking deviates from normal. Higher NI values indicate more severe abnormalities. Results: There was no significant correlation between NI and FA values of the right or left side calculated separately. However, there was a strong correlation between NI and combined FA values from the left and right side (table, * Spearman's Correlation rho = -.976 p≤.001 (2-tailed)). The combined FA values were examined because the NI represents the average of gait parameters on the right and left sides of the body. Conclusion: These preliminary findings suggest a link between neonatal brain MRI abnormalities and later gait abnormalities.